Child's play influence of animated programs on the group play behavior of Filipino preschool children - De La Paz, Sharon Rachel F.
This qualitative thesis is a descriptive and exploratory study that delved into and described the animated programs that preschool children watched and the influence of such programs on their group play behavior in the school environment. This study sought to answer how animated programs influenced the games children played and the manner of interaction with their peers. Observations of actual group play behavior in school; focus interviews with preschool students, and teachers; and textual analyses of popular Japanese anime or cartoons were conducted. Results of the study showed that preschool students were influenced by animated programs in their group play behavior. Influence was manifested through role-playing, such as assuming the character's identity and mimicking his movements and imitation of sound effects and music heard in the program while playing. Elements of the program, particularly characters and events, are incorporated into games such as mock battles and chanting in hand games. The fact that other preschool children can easily identify with the program or character being acted out shows that children are more or less exposed to the same kind of programs. This common exposure and interaction with their peers allows them to create collective meanings and rules about the games and animated programs.